2007
DOI: 10.1111/j.1872-034x.2007.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Double filtration plasmapheresis and interferon combination therapy for chronic hepatitis C patients with genotype 1 and high viral load

Abstract: DFPP plus IFN combination therapy produced a great reduction of viral load during the early stage of treatment and achieved a high sustained virus response, suggesting that this combination therapy may be a new modality for chronic hepatitis C patients at difficult-to-treat states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 31 publications
4
54
1
2
Order By: Relevance
“…Several studies have reported the use of DFPP for HCV treatment [4][5][6]. Fujiwara et al [4] demonstrated that DFPP plus IFN combination therapy produced a considerable reduction in the viral load during the early stage of treatment and yielded a high SVR rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported the use of DFPP for HCV treatment [4][5][6]. Fujiwara et al [4] demonstrated that DFPP plus IFN combination therapy produced a considerable reduction in the viral load during the early stage of treatment and yielded a high SVR rate.…”
Section: Discussionmentioning
confidence: 99%
“…Fujiwara et al [4] demonstrated that DFPP plus IFN combination therapy produced a considerable reduction in the viral load during the early stage of treatment and yielded a high SVR rate. Subsequently, Namba et al [5] also reported the use of DFPP plus IFN combination therapy to reduce HCV RNA blood levels in the early stage of IFN therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combination of DFPP and IFN also achieved impressive SVR in difficult-to-treat patients (i.e., relapsed, nonresponder, or HIVcoinfected patients) [181][182][183][184] and may also be safe for the elderly population [185]. However, the approach of apheresis for decreasing HCV viral load requires specialty equipment and possesses potential risk of adverse events (e.g., blood pressure lowering, puncture site hematoma, or infection) [181,185].…”
Section: Therapeutic Apheresis For the Removal Of Hcv Virionsmentioning
confidence: 99%